DIDACTIC ENGINEERING OF THE IT-DISCIPLINE’s CONTENT OF PEDAGOGICAL EDUCATION - Tychonova, Т.В. (Journal of Information Technologies in Education (ITE), 2013)
The author substantiates the content of stages of the didactic engineering of information technology discipline in higher pedagogical education.